Genetic polymorphism of four candidate genes in dairy cattle of Kashmir, India - SHAH, RUKSANA; GANAI, N A; SHANAZ, S; SHEIKH, F D; KHAN, H M; KHAN, NUSRAT N; HAMADANI, AMBREEN; ALAM, SAFEER (The Indian Journal of Animal Sciences, 2021)
Genetic information is necessary to devise strategic plans aimed to improve the genetic merit of dairy cattle. Exploration of quantitative, qualitative, and molecular genetics is important to improve dairy cattle performance. The aim of the study was to detect the presence of and to identify the polymorphism of kappa-casein (κ-CN), betalactoglobulin (β-LG), prolactin (PRL) and pituitary inhibition factor 1 (PIT-1) in 120 dairy cows of two genetic groups; Jersey and crossbred HF cows (60 each) maintained at an organized farm in Kashmir. PCR-RFLP of all selected candidate genes revealed ‘KK’, ‘Kk’ and ‘kk’ for HF crossbred cows and ‘KK’ and ‘Kk’ genotypes in Jersey cows for κ-CN gene. All animals under study showed 2, viz. Bb and bb genotypes for β-LG gene. In crossbred cows, all 3 patterns ‘RR’, ‘Rr’ and ‘rr’ were present but in Jersey cows, the genotype ‘rr’ was absent for PRL gene. In the genetic groups under study, 2 genotypes ‘Pp’ and ‘pp’ were found for PIT-1 gene. Genotypes Kk, Bb, Rr and pp were most prevalent in our selected population for κ-CN, β-LG, PRL and PIT-1 genes, respectively. Frequencies of K, b, R and p were found to be high for κ-CN, β-LG, PRL and PIT-1 genes, respectively. Chi-square analysis and p-values showed that the population does not vary significantly and proves that the population is in equilibrium. Our populations of Jersey and crossbred Friesian Holstein cattle were polymorphic. Genotypes Kk, Bb, Rr and pp were most prevalent in our population for κ-CN, β-LG, PRL and PIT-1 genes, respectively. The Chi-square and p-values showed that the population does not vary significantly and proves that the population is in equilibrium.